2016
DOI: 10.1016/j.apjtm.2016.01.018
|View full text |Cite
|
Sign up to set email alerts
|

First histopathological study in kidneys of rodents naturally infected with Leptospira pathogenic species from Yucatan, Mexico

Abstract: The histopathological lesions are present in the kidneys, plus the results of the polymerase chain reaction confirm that these rodents are true carriers of Leptospira spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
1
3
0
9
Order By: Relevance
“…The histological changes described in the present study are similar to those found by Carvalho and collaborators [11] in sheep and by Torres-Castro et al, [47] in rodents, in relation to the evidence of interstitial nephritis. In leptospirosis, inflammatory infiltrate is a primary alteration during acute renal injury and can be caused by direct damage by leptospires to the host tissue or by the presence of leptospiral antigen, initiating a renal immune response [36].…”
Section: Discussionsupporting
confidence: 92%
“…The histological changes described in the present study are similar to those found by Carvalho and collaborators [11] in sheep and by Torres-Castro et al, [47] in rodents, in relation to the evidence of interstitial nephritis. In leptospirosis, inflammatory infiltrate is a primary alteration during acute renal injury and can be caused by direct damage by leptospires to the host tissue or by the presence of leptospiral antigen, initiating a renal immune response [36].…”
Section: Discussionsupporting
confidence: 92%
“…Los infiltrados celulares inflamatorios presentes se clasificaron según su porcentaje de afección en tejido en: leve (<30%), moderado (30-50%) y severo (>50%), según lo establecido por Torres-Castro et al (2016). Los patrones de distribución fueron reportados según lo propuesto por Trigo & Valero (2004): focal: un solo sitio afectado; multifocal: varios sitios afectados, separados por tejido sano y normal, y zonal: un área total afectada.…”
Section: Estudio Histológicounclassified
“…This work is the first approximation to the study of Leptospira in rodents in the northern part of the state of Veracruz. Besides, it represents the first molecular confirmation of the presence of L. borgspetersenii in rodents, particularly in Mus musculus, in México (Espinosa-Martínez et al 2015;Torres-Castro et al 2016Panti-May et al 2017). The reference serovar of L. borgspetersenii isolated from M. musculus is Ballum, which was detected in the past century in Europe (Yager et al 1953).…”
Section: Discussionmentioning
confidence: 87%
“…In México, few studies have been conducted to detect Leptospira sp. in rodents, mostly in the states of Tamaulipas, Campeche, and Yucatán (Méndez et al 2013;Espinosa-Martínez et al 2015;Torres-Castro et al 2016; Panti-May et in each locality. The rodents captured were removed from traps, identified, and processed for kidney sample collection following biosafety standards, under collection license FAUT-0250 granted by the Secretariat of Environment and Natural Resources (Semarnat).…”
Section: Introductionmentioning
confidence: 99%